ANALISA STRUKTUR MIKRO TERHADAP PADUAN AL-CU HYPOEUTEKTIK - Wahid, Ichlas; Rohman Sayuti, Abdur (MEKANIKA: Jurnal Teknik Mesin, 2017)
This study analyzes the temperature of casting and mold temperature which must have aneffect on the existing structure of the material. The hypoutectic Al-Cu is an aluminum andcopper alloy with an eutectic phase which has the advantage of melting and pouring(especially around the eutectic region) at a temperature of 548 ° C. Aluminum is one of thereactive metal which is easily oxidized with oxygen to form a layer of aluminum oxide,alumina (Al2O3) which can make it good corrosion resistant. However, if the levels of Fe, Cuand Ni are added can reduce the corrosion-resistant properties because the alumina contentdecreases. Copper can form the correct eutectic with aluminum at levels of 33%. Copperalloys (Al / Cu) containing 10-20% Al indicate exceptional strength, for hardness and wear,adjusting of some steel alloys. By using gravity casting method permanent mold will be easilydismantled pairs. The material composition is 3.375 gram aluminum and 1,125 gram ofcopper. The pouring temperature used was 600 ° C, 650 ° C, and 700 ° C while the moldtemperature used was room temperature, 100 ° C, and 200 ° C. The specimen is divided intoA ', B, and A' codes at the time of cutting using lathe and freis. Pouring temperature andmold temperature will affect the microstructure formed. The higher the pouring temperature,the clearer the structure will be, visible at the pouring temperature of 700 ° C. And thesmaller the mold temperature the rougher the shape of the structure, the outward appearanceis apparent, and it can be said that a dendrite structure is formed. Codefication B is the coreor midpoint of the mold is the farthest point of the cooling rate process, the structure formedin the B-code is clear, thick and coincident.